Dietary zinc intake associated with stroke in American adults - Wu, Xiaoke; Shi, Mengmeng; Zhang, Haifeng; Fang, Shaokuan (Scientific reports, 2025)
Evidence on the relationship between dietary zinc intake and stroke in American populations is limited. This study aimed to investigate the association between dietary zinc consumption and stroke prevalence among US adults. This cross-sectional study analyzed data from adults (≥ 18 years) who participated in the National Health and Nutrition Examination Survey (NHANES) between 2013 and 2020. Dietary zinc intake, stroke history, and other relevant factors were examined. Logistic regression models were used to assess the association between dietary zinc consumption and stroke risk, while restricted cubic splines (RCS) were applied to explore potential non-linear relationships. A total of 2642 adults from four NHANES cycles (2013–2020) were included in the analysis. In multivariate logistic regression, individuals in the second quartile of dietary zinc intake (Q2: 6.09–8.83 mg/day) had a significantly lower odds ratio (OR) for stroke (OR = 0.64, 95% confidence interval (CI) 0.41–0.99, p = 0.044) compared with those in the lowest quartile (Q1: ≤6.08 mg/day). RCS analysis indicated an L-shaped relationship between dietary zinc intake and stroke odds ( p = 0.041). Threshold analysis revealed that for individuals consuming less than 8.82 mg of zinc daily, the OR for stroke was 0.858 (95% CI 0.74–0.99, p = 0.037). Our findings suggest an L-shaped association between dietary zinc intake and stroke prevalence in American adults, with higher zinc intake associated with lower odds of stroke within a specific intake range.